Korean Architecture : breathing with nature (Korea essentials, 2012)
This book offers an introduction to Korea's abundant and unique architectural past and present, combining explanations of the principles behind Korean architecture with introductions to some of the country's finest buildings and structures. It explains some of the ideologies and perspectives that form the foundation of Korean architectural tradition and outlines the history of Korean architecture, from the first architectural traces of dugouts and lean-tos to the increasingly sophisticated wooden frames and technologies.